Mollusca Diversity in The Ora Beach Ecotourism Area of Saleman Village, Central Maluku District - Pary, Cornely; Mutmainnah, Heni; Aloatuan, Jumiati; Kurnia, Tri Santi (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2025)
Maluku is an archipelago rich in natural resources. One of area rich in marine biota among other villages in Central Maluku is Saleman Village. In the waters of Saleman village there are abundant molluscs. Therefore, this study aims to determine the density and diversity of mollusks. The research method used was descriptive qualitative with purposive sampling. Furthermore, identification and calculation of the diversity index were carried out. The researchers identified nine species with a total of 41 individuals. The species obtained were Anadara granosa, Meretrix lyrata, Semele cordiformis, Placuna placenta, Lambis lambis, Olividae, Tridacna maxima, Strombus Luhuanus L, and Conus aulicus L. The Diversity Index value obtained is 2.088. Therefore, the diversity index in the coastal watershed of Saleman Village is classified as medium.